(untitled) (Zdravstveni glasnik, 2024)
Resilience can be changed and modified over time, it is affected by many different situations and difficulties that a person overcomes during life. Resilience is a newer concept, which should be applied to the patient from the beginning of life with cancer. Clinicians should invest more time and effort in creating interventions that enable patients to foster their resilience. The term resilience or the ability to recover refers to the process of overcoming adverse events, including stress, trauma and illness. Considering the ability to recover as a personality trait imposes the assumption that the ability to recover represents a constellation of personal characteristics that enable individuals to adapt to different circumstances they encounter. Resilience as a complex phenomenon changes over time and circumstances. Understanding resilience as a complex, multidimensional and dynamic process is very important for understanding therapeutic mechanisms and healing mechanisms. Psychological factors are the most important factors that contribute to the development of resilience. It is necessary to work on the development of psychosocial interventions that will target the psychological resilience of cancer patients. Breast cancer is the most common malignant disease in women. In women with breast cancer who manage to develop the ability to resist and accept life’s crisis, greater resilience and personal growth is created, thereby reducing the negative impact associated with the disease. The aim of this work is to explain the relationship between resilience and breast cancer.